Jacobs Syndrome Presenting With Delayed Puberty and Central Hypogonadism: A Rare Case Report - Muhammad Hassaan Javaid; Ayesha Ahmad; Amna Ahmad; Muhammad Ajmal Khamosh; Muhammad Hanzla (Clinical Case Reports, 2026)
ABSTRACT In some rare instances, patients with 47,XYY syndrome can be short in height, accompanied by hypogonadism without the characteristic tall stature. In cases where there is delayed puberty and unusual growth pattern, a complete endocrine work‐up, including GnRH and hCG stimulation tests, along with chromosome studies, is vital.